Factors affecting residual lesion in women with cervical adenocarcinoma in situ after cone excisional biopsy. - Srisomboon J. (2014)
The objective of this study was undertaken to evaluate the factors affecting residual lesion in women with adenocarcinoma in situ (AIS) on cervical conization specimens. The medical records of women with AIS who had no associated invasive carcinoma after cervical conization and underwent subsequent hysterectomy at Chiang Mai University Hospital were reviewed. During March 1998 and March 2006, 45 women were included for analysis. The mean age was 45.2 years (range, 30-66 years). Thirteen (28.9%) women presented with AIS on Pap smear. Thirty (66.7%) underwent loop electrosurgical excision procedure and the remaining 15 (33.3%) underwent cold-knife conization. Twenty (44.4%) women had mixed lesions of AIS and squamous intraepithelial lesion on cervical specimens. Surgical cone margins were clear in 25 (55.6%) women. Eighteen (40%) and two (4.4%) women had involved and non-evaluable cone margins, respectively. Residual lesion was noted in 14 (31.1%) hysterectomy specimens. There was no residual lesion in women with clear cone margins while 72% and 50% of women with involved and non-evaluable cone margins, had residual lesion, respectively. These differences were statistically significant (P<0.001). No significant association between the ECC results and the residual lesion was noted (P=0.29). In conclusion, approximately one-third of women with AIS on cervical conization have residual lesion on subsequent hysterectomy specimens. Only cone margin status is a significant predictor for residual lesion.